Experimental study on charge air heat utilization of large-scale reciprocating engines by means of Organic Rankine Cycle. (5th October 2015) - Uusitalo, Antti; Honkatukia, Juha; Backman, Jari; Nyyssönen, Sami
Abstract: Power systems based on Organic Rankine Cycle (ORC) technology have been recognized as one of the most promising solutions in converting low- and medium-temperature heat into electricity. In this paper, experimental results of the utilization of charge air heat by means of ORC are presented. The experimental setup consists of a 1.6 MW e diesel engine and an ORC process utilizing charge air heat in which the turbine-generator has been replaced with an expansion valve. Thus, no mechanical or electrical power was extracted from the system and the primary focus of the experiments was to study the performance of the evaporator acting as a charge air cooler. The studied working fluids were R245fa and isopentane. The test runs were carried out at full engine load and at engine part loads. In addition, transient tests were carried out. Based on the measured values the ORC utilizing charge air heat was evaluated to be capable to increase the power output of the test engine by 2%. Highlights: Utilization of charge air heat by means of ORC was studied. Experimental study was carried out at design, off-design, and transient conditions. The performance of the cycle was studied with two different fluids. The use of ORC was estimated to increase the power output of the engine by 2%.